Advances in Nanotechnology for Enhancing the Solubility and Bioavailability of Poorly Soluble Drugs - Liu Y; Liang Y; Yuhong J; Xin P; Han JL; Du Y; Yu X; Zhu R; Zhang M; Chen W; Ma Y (Dove Medical Press, 2024)
Yifan Liu,1 Yushan Liang,2 Jing Yuhong,3 Peng Xin,1 Jia Li Han,4 Yongle Du,5 Xinru Yu,3 Runhe Zhu,6 Mingxun Zhang,6 Wen Chen,7 Yingjie Ma7 1School of Medicine, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 2School of Rehabilitation Medicine, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 3School of Pharmacy, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 4School of Health Sciences, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 5School of Ophthalmology and Optometry, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 6School of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 7First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of ChinaCorrespondence: Yingjie Ma; Wen Chen, The First Clinical College, Shandong University of Traditional Chinese Medicine; Reproductive and Genetic Center of Integrative Medicine, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, 42, Wenhua Road (W), Lixia District, Jinan, 250014, People's Republic of China, Email 545914553@qq.com; wenchen0515@163.comAbstract: This manuscript offers a comprehensive overview of nanotechnology's impact on the solubility and bioavailability of poorly soluble drugs, with a focus on BCS Class II and IV drugs. We explore various nanoscale drug delivery systems (NDDSs), including lipid-based, polymer-based, nanoemulsions, nanogels, and inorganic carriers. These systems offer improved drug efficacy, targeting, and reduced side effects. Emphasizing the crucial role of nanoparticle size and surface modifications, the review discusses the advancements in NDDSs for enhanced therapeutic outcomes. Challenges such as production cost and safety are acknowledged, yet the potential of NDDSs in transforming drug delivery methods is highlighted. This contribution underscores the importance of nanotechnology in pharmaceutical engineering, suggesting it as a significant advancement for medical applications and patient care.Keywords: nanotechnology, solubility and bioavailability, poorly soluble drugs, drug delivery systems, pharmaceutical engineering